Modification of Activated Carbon from Palm Kernel Shells with Fe₃O₄ Magnetic for Water Treatment of Enim River - Damayanti Damayanti; Susila Arita; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
The economical, easy-to-implement, and regenerative treatment methods are essential to obtain clean water. In this study, activated carbon was synthesized from palm kernel shells using ZnCl₂ as an activator. The activated carbon was then modified with Fe₃O₄. The resulting activated carbon and activated carbon-Fe₃O₄ product were characterized using XRD, SEM-EDX, VSM, and BET surface area analysis. Furthermore, activated carbon-Fe3O4 was applied to reduce Fe ions, turbidity, and total suspended solids (TSS) and increase the pH value in Enim river water. The resulting activated carbon has met SNI standards, with a moisture content of 8.81%, ash content of 5.475%, and an iodine adsorption capacity of 1763.86 mg/L. The synthesized activated carbon-Fe₃O₄ exhibits strong magnetic properties, with a saturation magnetization value of 68.82 emu/g and a surface area of 355.42 m²/g. Optimal conditions for the treatment of Enim river water were obtained at an adsorbent dose of 40 mg/L, a stirring rate of 120 rpm, and a stirring time of 120 minutes. Under these conditions, the Fe ion reduction efficiency reached 96.95%, turbidity 89.83%, and TSS 80.74%, while the pH increased from 6.23 to 6.74. FTIR analysis showed a change in peak intensity in the activated carbon-Fe₃O₄ after the adsorption process, indicating interaction with contaminants. The adsorption process of Fe ions by activated carbon-Fe₃O₄ follows a pseudo-second-order kinetic model.